2009
DOI: 10.1158/0008-5472.can-08-3718
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of Suppressed RhoB is a Critical Step for the Inhibition of Anaplastic Thyroid Cancer Growth

Abstract: Anaplastic thyroid carcinoma (ATC) is a highly aggressive form of the disease for which new therapeutic options are desperately needed. Previously, we showed that the highaffinity peroxisome proliferator-activated receptor ; (PPAR;) agonist, RS5444, inhibits cell proliferation of ATC cells via induction of the cyclin-dependent kinase inhibitor p21 WAF1/CIP1 (p21). We show here that up-regulation of RhoB is a critical step in PPAR;-mediated activation of p21-induced cell stasis. Using multiple independently der… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 41 publications
2
52
0
Order By: Relevance
“…Therefore, histone modifications or other transcriptional regulatory mechanism may be responsible for the loss of RhoB expression. Preclinical data suggest increased histone acetylation at the RhoB promoter region results in its reexpression in lung carcinoma and anaplastic thyroid cancer (30,34). In our study, the combination treatment resulted in significant histone H3 acetylation at the promoter region of RhoB gene compared with romidepsin alone suggesting histone acetylation is responsible for transcriptional activity of RhoB, which is further enhanced by the hypomethylating agent azacitidine.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Therefore, histone modifications or other transcriptional regulatory mechanism may be responsible for the loss of RhoB expression. Preclinical data suggest increased histone acetylation at the RhoB promoter region results in its reexpression in lung carcinoma and anaplastic thyroid cancer (30,34). In our study, the combination treatment resulted in significant histone H3 acetylation at the promoter region of RhoB gene compared with romidepsin alone suggesting histone acetylation is responsible for transcriptional activity of RhoB, which is further enhanced by the hypomethylating agent azacitidine.…”
Section: Discussionsupporting
confidence: 54%
“…This might be due to the fact that DNA hypomethylation results in a more accessible chromatin for histone acetylation or due to DNA hypomethylation-independent effects of azacitidine that could contribute to the synergistic effects of the combination. It is suggested that RhoB promotes cell-cycle arrest by controlling the expression of cell-cycle regulators such as p21 (34). We observed an upregulation of p21 in cell lines and tumor cells derived from S ezary syndrome patients.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…It has also been shown to sensitize a human anaplastic thyroid cancer (ATC) cell line to doxorubicin (Kitazono et al 2002). Depsipeptide induces RhoB activity, which leads to upregulated p21 expression that attenuates cell proliferation (Marlow et al 2009). Valproic acid strongly suppresses the growth of poorly differentiated thyroid cancer cell lines by inducing apoptosis and cell cycle arrest (Catalano et al 2005(Catalano et al , 2006.…”
Section: Rarb2mentioning
confidence: 99%
“…PPAR-g plays a variety of roles in adipose cell differentiation, modulation of metabolism, and the inflammatory response (2,3). The protein interacts with and/or regulates multiple signaling pathways, including those associated with p21Cip1 (4,5) and p27 (6,7) to regulate the cell cycle, with nuclear factor kappa b (8) to reduce the expression of cytokines such as interleukin-6, and interleukin-8, and with cyclooxygenase-2 and prostaglandin E2 to suppress inflammation (9,10). Genetic studies have indicated that PPAR-g functions as a tumor suppressor in a variety of tissues, including the breast (11), prostate (12), and colon (13).…”
Section: Introductionmentioning
confidence: 99%